Respuesta :

Answer:

Step-by-step explanation:

Sum  = 6

Product = -72

Factors = 12 , (-6)    {12 +(-6) = 6  & 12*(-6) = -72}

9a² + 6a - 8 = 9a² + 12a - 6a - 8  

                  = 3a(3a + 4) - 2(3a +  4)

                  = (3a + 4)(3a - 2)

Hint: 9a² + 12a = 3a*a + 3a*4  = 3a(3a + 4)

-6a - 8 = -2 * 3a - 2 * 4 = -2(3a + 4)

Answer:

(3a-2)(3a+4)

Step-by-step explanation:

9a^2+6a-8

9a^2+(12-6)a-8

9a^2+12a-6a-8

3a(3a+4)-2(3a+4)

(3a+4)(3a-2)...factors

Hope it Helps you!!

ACCESS MORE